Review of related literature on problem-based learning and cognitive apprenticeship for instruction in agriculture as vocational education - Girei, Mohammed Musa (HRMARS, 2020)
Problem-based learning (PBL) is a student-centered, enabling approach for fostering student’s collaboration, self-directed learning, and critical reasoning skills. This paper discussed the previous literature on how components of problem-based learning (PBL) integrates Cognitive apprenticeship (CA) learning principle, considering Scaffolding could benefit vocational learning in the field of Agriculture. These are elements employed to expose students to real-world problem solving, critical thinking skills as well as effective knowledge transfer through active engagement. Results indicate that undertaking on the role of a more specialist as an instructor can take a dynamic role in the problem-based learning strategy, providing the necessary resources to build learners who could address ill-structured problems to use the application of real-life experience and specialist-level strategies to address the cognitive task. This complex skill that cannot be acquired through the traditional teaching, but rather skills that are acquired through the scaffolding of progressive and more stimulating learning opportunities, through guidance and routine exercise, collaborative, and self-reflection. Solving real-world problems entails active collaboration and exploiting the potentials of technologies available for us, and thus instructors need to be contentedas facilitators of a learning situation that is often a complex and challenging environment. Thus, it is established that the PBL and Scaffolding have the potentials to enhance student's critical thinking skills but with a careful structure of authentic learning situations.